Study on prevalence of bovine diseases at sadar upazila in dinajpur district of Bangladesh - Mohammed, Moktar Omar; Rahman, Md Shajedur; Hoque, Md Fazlul; Rumi, Nazmi Ara; Afrah, Osman Hassan (Asian Journal of Medical and Biological Research, 2018)
The study was conducted to investigate the status of cattle diseases with relation to seasonal variation in Dinajpur district of Bangladesh. A total of 11402 clinical cases were registered for the clinical diagnosis and therapeutic purposes at sadar upazila veterinary hospital in Dinajpur district of Bangladesh during the period of March, 2016 to February, 2017. Disease diagnosis was made on the basis of owner’s statement, general examination and clinical signs. Diagnosed diseases were categorized as general clinical disorders, parasitic diseases, viral diseases, bacterial diseases, venereal disease, and metabolic disorders. According to study the highest (64.15%) prevalence was by parasitic disease followed by bacterial diseases (10.67%), viral diseases (8.97%), metabolic disease (7.61%), and venereal disease (6.60%). In respect of seasons, the prevalence of both bacterial diseases and viral diseases were significantly (p<0.01) higher (13.88%) and (12.10%) in summer season respectively. Whereas the parasitic diseases were significantly (p<0.01) higher (68.65%) in winter season. On the basis of season, it was found that the overall prevalence of diseases was highest in summer season (47.87%) followed by rainy season (30.10%) and comparatively lower in winter season (22.03%). Asian J. Med. Biol. Res. December 2017, 3(4): 446-453